Tworzenie obrazu przeszłości w trylogii robotniczej Andrzeja Wajdy - Kornacki, Krzysztof (Przestrzenie Teorii, 2017)
Observing the process of the birth of Man of Marble – Man of Iron – Wałęsa. Man of Hope trilogy we can clearly see the author’s increasing tendency to render movie fiction real, in the sense that fiction should be treated as reality, as its equivalent. In the two first films in the trilogy, what is visible is the intensified blurring of the lines between fiction and reality, substituting what is fact with something concocted. What we can also see here is a tendency to boost the credibility of a fictional story, thanks to the use of conventions and documentary materials. Gradual changes made in the sphere of art were connected with the director’s public activities, in which he gradually crossed the boundaries not only of social, but also political praxis. Moreover, in creating the trilogy we can see a voluntaristic trend to perceive the past as the history of “great men” and to canonize the glorious image of history. All these tendencies were expressed in the latter work. Wajda completed this as a clear response to political moves by certain politicians and historians attacking Wałęsa. Preparing a movie about him, he approached verification of historical data with a single-minded attitude. Thus in this film we can observe “true fabrications”. Wałęsa pervades the story, and there is no room for other important figures in the historical process. Additionally, in order to create an imagined, idealistic image of Wałęsa (“Wałęsa 2.0”), the actor playing this role “expels him” from the archive material.